Differential diagnosis of classical Bartter syndrome and Gitelman syndrome: Do we need genetic analysis? - ALAVANDA, CEREN; ALPAY, HARİKA; GÖKCE, İBRAHİM; SAK, MEHTAP; YILDIZ, NURDAN; ATA, PINAR (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: Classical Bartter syndrome (cBS) and Gitelman syndrome (GS) are genotypically distinct, but there is a phenotypic overlap among these two diseases, which can complicate the accurate diagnosis without genetic analysis. This study aimed to evaluate the correlation between clinical and genetic diagnoses among patients who have genetically defined cBS and GS. Patients and Methods: The study included 18 patients with homozygous/compound heterozygous CLCNKB (NM_000085) (n:10/18) and SLC12A3 (NM_000339) (n:8/18) mutations. Biochemical, clinical and radiological data were collected at presentation and at the last visit. Results: In cBS group age at diagnosis, median plasma potassium and chloride concentrations were significantly lower and median plasma HCO3 and blood pH values were significantly higher. Patients with GS had significantly lower median plasma magnesium concentrations and urinary calcium/creatinine ratio. One child with GS had normocalciuria, two children with cBS had hypocalciuria and hypomagnesemia. Low estimated glomerular filtration rate (eGFR) (ml/dk/1.73m2) and growth failure were more evident in cBS group. In patients with cBS, nine different CLCNKB gene mutations were detected, five of them were novel. Novel mutations were: one nonsense (c.66G>A, p.Trp22*), one missense (c.499G>A, p.Gly167Ser) and three splice-site (c.867-2delA; c.499-2insG; c.19302A>C) mutations. In patients with GS, six different SLC12A3 gene mutations were found. Conclusions: It may not always be possible to clinically distinguish cBS from GS. We suggest to perform a genotypic classification if genetic analysis is possible.
Keywords: Bartter syndrome; Gitelman syndrome; Kidney tubuler disease; Hypokalemic metabolic alkalosis; CHLORIDE CHANNEL GENE; HYPOKALEMIC ALKALOSIS; MUTATIONS; CLCNKB; SPECTRUM; VARIANTS